Ubiquitin-Like Protein UBD Promotes Cell Proliferation in Colorectal Cancer by Facilitating p53 Degradation - Su, Hongbin; Qin, Mengdi; Liu, Qiang; Jin, Bo; Shi, Xianjun; Xiang, Zheng (Frontiers in Oncology, 2021)
Purpose: Ubiquitin D (UBD) is a member of the ubiquitin-like modifier (UBL) family and is highly expressed in a variety of cancers including colorectal cancer (CRC). However, the mechanisms of its regulatory roles in CRC are largely elusive. In this study, we revealed the effect of UBD on the proliferation of CRC. Methods: The expression of UBD in clinical tissue samples of CRC and seven CRC cell lines was detected using qRT-PCR, immunohistochemistry (IHC) and Western blotting. CCK-8, colony formation, EdU and flow cytometry assays were used to detect the functional changes of CRC cells transfected with UBD stable expression plasmids in vitro. A xenograft model was constructed to assess the effect of UBD on the growth of CRC cells in vivo. The connection between UBD and p53 was analyzed using Western blotting, immunoprecipitation, proteasome inhibition assay and Cycloheximide (CHX) chase assay. Results: UBD was overexpressed in CRC tumor tissues compared with nontumor tissues, and its overexpression was positively associated with the tumor size and TNM stage of CRC patients. Functionally, UBD significantly accelerated CRC cell viability and proliferation in vitro and promoted tumorigenesis in vivo. Mechanistically, UBD interacted with p53 in CRC cells, downregulated the expression of p53 by regulating its degradation, shortened the p53 half-life, thereby further affecting the decrease in p21 and the increase in Cyclin D1, Cyclin E, CDK2, CDK4 and CDK6. Moreover, in vivo experiments showed that UBD-induced tumor growth in nude mice was dependent on a decrease in p53. Conclusions: Our study proved that UBD mediates the degradation of p53, thereby facilitating the growth of CRC cells and ultimately promoting the progression of CRC. Therefore, UBD may be a potential therapeutic target and a promising prognostic biomarker for CRC.